Os Choros de Belini Andrade: estilo composicional e suas implicações na performance musical - Leonardo Barreto Linhares (2016)
Study on the compositional style of the composer-instrumentalist Belini Andrade (n.1920) from Minas Gerais, Brazil, from the perspective of style analysis (LA RUE, 1992), comparative analysis (COOK, 1987), performance practices and hermeneutics (PALMER, 1986 ; BLACKING, 2007), and its implications for the interpretation of the choro, his favorite genre. The identification of less recurring elements within the choro tradition in relation to melody, harmony, rhythm and form (ALMADA, 2006; ALMEIDA, 1999; PRINCE, 2011; SANTOS, 2002; SÈVE, 1999) explains the fame of a virtuosic, idiomatic and challenging music, peripheral to the Brazilian rodas de choro [improvisation choro groups], while yielding great unity to the corpus of his work, which includes 348 edited choros and four albums recorded to date. Methodological procedures of this research include the recording and release of the CD Chorando com Belini: os choros de Belini Andrade por vários intérpretes [Crying with Belini: Belini Andrades choros with several performers] which aims at demonstrating the analysis results promoting his works inside and outside of the academic circles